2010
DOI: 10.1007/s12529-010-9138-1
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviours as Mediating Pathways between Socioeconomic Position and Body Mass Index

Abstract: The strongest indirect associations between socioeconomic position and BMI were mediated through variables related to energy balance, i.e. diet and sedentariness. To reduce the socioeconomic variation in overweight and obesity, the main focus should be on food and sedentary behaviours while also taking into account the gender differences and clustering of unhealthy behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 46 publications
(100 reference statements)
3
29
2
2
Order By: Relevance
“…Interestingly, educational level did not associate with food or nutrient intake in this study, even when it is known that socioeconomic position can influence health behaviour, especially eating habits 36. We speculate that shift work itself may affect food habits more than education.…”
Section: Discussioncontrasting
confidence: 71%
“…Interestingly, educational level did not associate with food or nutrient intake in this study, even when it is known that socioeconomic position can influence health behaviour, especially eating habits 36. We speculate that shift work itself may affect food habits more than education.…”
Section: Discussioncontrasting
confidence: 71%
“…The health examination of the 7784 participants included measurement of height and weight by a trained nurse at the local health care centre [20,25]. BMI was calculated as weight (in kilograms) divided by height (in meters) squared.…”
Section: Measurementsmentioning
confidence: 99%
“…(Borodulin et al, 2010). The results of this study showed that the children who were in low socio-economic level were mainly in moderate activity zone and mainly ranked as normal BMI level.…”
Section: Discussionmentioning
confidence: 61%